2016
DOI: 10.5194/nhess-2016-133
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

New insights into flood warning and emergency response from the perspective of affected parties

Abstract: Abstract. Early warning is essential for protecting people and mitigating damage in case of flood events. However, early warning is only helpful if the parties at risk are reached by the warning, if they believe the warning and if they know how to react appropriately. Finding suitable methods for communicating helpful warnings to the "last mile" remains a challenge. To gain more knowledge, surveys were undertaken after the August 2002 and the June 2013 floods in Germany, asking affected private households and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…However, an impact‐based flood warning as it exists in England is not available in Germany. Nevertheless, only 7% of affected residents did not receive a warning in the June 2013 floods in contrast to 27% in 2002 [ Kreibich et al, ]. Residents were also better informed about PLPMs [ Thieken et al, ].…”
Section: Analysis Of How Flood Insurance Contributes To Flood Risk Rementioning
confidence: 99%
“…However, an impact‐based flood warning as it exists in England is not available in Germany. Nevertheless, only 7% of affected residents did not receive a warning in the June 2013 floods in contrast to 27% in 2002 [ Kreibich et al, ]. Residents were also better informed about PLPMs [ Thieken et al, ].…”
Section: Analysis Of How Flood Insurance Contributes To Flood Risk Rementioning
confidence: 99%
“…In this review, 6 out of 24 barriers have been identified as social factors. A lack of public awareness of understanding the warning information is the most highlighted barrier cited by many researchers [10,12,20,21,25,34,35,[38][39][40]46]. The absence of knowledge and awareness of understanding the warning message [12,21,38] and the lack of community understanding on how to respond to the warnings [10,20,39,46] and minimising the impact [48] have been highlighted by several researchers.…”
Section: Social Factorsmentioning
confidence: 99%
“…A lack of public awareness of understanding the warning information is the most highlighted barrier cited by many researchers [10,12,20,21,25,34,35,[38][39][40]46]. The absence of knowledge and awareness of understanding the warning message [12,21,38] and the lack of community understanding on how to respond to the warnings [10,20,39,46] and minimising the impact [48] have been highlighted by several researchers. Rana et al [25] argue that technical jargon and the complexities of official warning messages may inhibit a better understanding of warning messages.…”
Section: Social Factorsmentioning
confidence: 99%
“…DMO agents have to decide (a) which task and (b) which target site to choose. In reality, DMOs rarely have the time to derive an optimal decision; they mostly rely on certain routines and past experiences (Kuhlicke 2010). In our model, DMO agents therefore employ simple heuristics in their decision making, based on their level of information access (partial or full knowledge) and their available resources (e.g., whether sandbag supply is sufficient or not).…”
Section: Dmo Movement and Decision Makingmentioning
confidence: 99%